2021
DOI: 10.1001/jamainternmed.2020.8193
|View full text |Cite
|
Sign up to set email alerts
|

Variation in US Hospital Mortality Rates for Patients Admitted With COVID-19 During the First 6 Months of the Pandemic

Abstract: IMPORTANCEIt is unknown how much the mortality of patients with coronavirus disease 2019 (COVID-19) depends on the hospital that cares for them, and whether COVID-19 hospital mortality rates are improving.OBJECTIVE To identify variation in COVID-19 mortality rates and how those rates have changed over the first months of the pandemic. DESIGN, SETTING, AND PARTICIPANTSThis cohort study assessed 38 517 adults who were admitted with COVID-19 to 955 US hospitals from January 1, 2020, to June 30, 2020, and a subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
264
6
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(318 citation statements)
references
References 15 publications
34
264
6
3
Order By: Relevance
“…Our study of more than 450 patients with COVID-19–related critical illness across 5 hospitals within an academic health system during the initial surge of the pandemic adds support to many findings published by other centers in the United States and globally ( 1–10 , 12 ), and offers some important additions to our rapidly evolving understanding of the epidemiology of this novel disease. These additions, as well as those in reports from other centers that continue to be released, are particularly important as the United States and other nations combat ongoing and new surges related to opening economies, reduced mitigation strategies, and seasonal changes, among other factors ( 18 ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our study of more than 450 patients with COVID-19–related critical illness across 5 hospitals within an academic health system during the initial surge of the pandemic adds support to many findings published by other centers in the United States and globally ( 1–10 , 12 ), and offers some important additions to our rapidly evolving understanding of the epidemiology of this novel disease. These additions, as well as those in reports from other centers that continue to be released, are particularly important as the United States and other nations combat ongoing and new surges related to opening economies, reduced mitigation strategies, and seasonal changes, among other factors ( 18 ).…”
Section: Discussionsupporting
confidence: 70%
“…We examined all-cause 28-day in-hospital mortality over 2 measures of health system COVID-19 experience: intervals of time and intervals of cumulative COVID-19 patient volume. Other studies have reported a learning effect ( 5 , 10 , 12 , 23 ). Our results support the notion that outcomes improved during the pandemic independent of patient-level factors.…”
Section: Discussionmentioning
confidence: 87%
“…(11) Studies have shown that a strain on hospital capacity has been associated with increased mortality in non-pandemic settings. (35) COVID-19 mortality in hospitals seems to be higher when the incidence of COVID-19 in the community was high or increasing (36,37) and when the number of hospitalisations were highest. (19) In addition, the rapid escalation in cases resulted in hospital resource constraints affecting outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There are several potential explanations for our findings. The overall decline in COVID-19 illness severity, with a reported mortality rate as high as 16.6% in January-April and declining to 9.3% by May-June, 26 has been associated with broadening demographics of the populations at risk, in addition to rapidly advancing therapeutics such as remdesivir, baricitinib and monoclonal antibodies. [27][28][29] As for other disease states, new therapeutics are often not available to all segments of society simultaneously and thus can exacerbate disparities in healthcare access, utilisation and outcomes.…”
Section: Discussionmentioning
confidence: 99%